Perception on the role of parenting styles and peer influence on juvenile delinquency among adolescents in the government remand homes in Lagos, Nigeria - Adewale, Yusuf Sodiq (2021)
Adolescence is a time in which a juvenile seeks autonomy and begin to develop their own identity. Some adolescents engage in activities that are both criminal and risky to their well-being. Juvenile delinquency has been a phenomenon sweeping across the entire globe. It has become a major concern of government, parents, schools, and society. To put it into perspectives, social scientists agreed that behaviours against the laws and societal norms are classified as delinquent behaviour. Researchers have attempted to explain the causes of delinquent behaviours, relating them to factors such as peer pressure, as well as family and school environment. The present study attempted to examine the perception of adolescents in the government remand homes, Lagos state, Nigeria on the link between parenting style, peer influence and juvenile delinquency issues. The research design is a descriptive correlational study. Data were collected through questionnaires. The variables in this research refer to parenting styles (abuse, indifferent and over control), peer influence and juvenile delinquency. In this study, the population was on the adolescents with delinquency issues who were placed at remand homes within Lagos state, Nigeria. The total populations consist of 216 juveniles from the three (3) government remand homes in Lagos state, which comprise both male and female members of the remand homes. The targeted population range between the ages of 10 – 18yrs. The sample size required was estimated by using a sample size formula proposed by Krejcie and Morgan (1977). The total sample size is 170 juveniles, comprising 146 males and 24 females of the remand homes. The findings show significant relationship between abuse parenting style and juvenile delinquency (r = 0.189, p < 0.05), and also shows that there is no significant relationship between indifferent parenting style and juvenile delinquency (r = 0.075, p > 0.05) and also no significant relationship between over control parenting style and juvenile delinquency (r = -.071, p > 0.05). Also, the multiple R (R= .285) revealed a significant moderate relationship between independent variable parenting style (indifference, abuse and over control), peer influence and dependent variable (juvenile delinquency). The regression analysis showed that parenting style and peer influence, jointly contributed 8.1% of the variance in juvenile delinquency, given the R2 0.081. This suggested that to improve adolescents’ behaviour, an effective parenting style is vital. This study found that there is no relationship between indifferent and over control parenting styles and juvenile delinquency. This finding indicates that Nigerian parents' traditional practice in their parenting process is acceptable to some extent from the adolescents' perspectives. One possible reason could be that the practice has been accepted as societal norms. The adolescents adjusted and accustomed to these practices due to consistent exposure to the norms since they were small. This finding further shows that urbanization has not significantly impacted how adolescents interpret their parents' ways of bringing up and educating them. However, abusive parental practice triggers antisocial behaviour. Consequently, it encourages adolescents to abandon their parents to seek emotional support from their peers. Hence, it was concluded that offensive and violence parenting could not be compromised, leading to more destructive consequences in adolescents. As an implication, parents should be encouraged to adopt the best parenting practices consistent with the adolescent’s psychological and behavioural development as well as consistent with their local culture, value, and practices. In terms of knowledge development, this present study contributes to bridging the literature gap concerning the role of parenting and peers' influence on juvenile delinquency among adolescents in Lagos, Nigeria.